5(x+5)=-5(1+4x)+25x

Simple and best practice solution for 5(x+5)=-5(1+4x)+25x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+5)=-5(1+4x)+25x equation:


Simplifying
5(x + 5) = -5(1 + 4x) + 25x

Reorder the terms:
5(5 + x) = -5(1 + 4x) + 25x
(5 * 5 + x * 5) = -5(1 + 4x) + 25x
(25 + 5x) = -5(1 + 4x) + 25x
25 + 5x = (1 * -5 + 4x * -5) + 25x
25 + 5x = (-5 + -20x) + 25x

Combine like terms: -20x + 25x = 5x
25 + 5x = -5 + 5x

Add '-5x' to each side of the equation.
25 + 5x + -5x = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
25 + 0 = -5 + 5x + -5x
25 = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
25 = -5 + 0
25 = -5

Solving
25 = -5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (x^2/5)/(x^2/3) | | 5(x+5)=-5(1+4x)+25 | | 3(x-2)-4x=-3(x+2)+2 | | 12t+6=-2(-6t-3) | | y=x^2+3x+0.25 | | .3y+.25=-.5y+.625 | | 10*cos(20*x)=x+2 | | 5x+8z=4+4y | | 2(5-1/2y)-7y=-6 | | (2x-1)=(x+31) | | t^3-3t^2+2t+4=0 | | 5x^2+2xy+2y^2-12x-6y+9=0 | | 7.7+8.1x=x+16.8 | | 6=.3x+5 | | 6x-54/7x-63 | | x/600=4/3 | | x/600=16/9 | | 2/(15-3x) | | 2x+x=46 | | 4(m-1)=24 | | 2/15-3x | | y^2-1/3x | | 7(w-1)=28 | | (5u-7)/(4u-12) | | 2(n-2)=20 | | 15=5h+5 | | -2z-5=-17 | | -6f+4=40 | | -g=44 | | 9-x=3/5 | | -9p+3=21 | | -1.7(a+18)=-0.7(a+19) |

Equations solver categories